CHD1L is associated with poor survival and promotes the proliferation and metastasis of intrahepatic cholangiocarcinoma - Li, Shimiao (Oncol Rep, 2019)
Chromodomain helicase/ATPase DNA-binding protein 1-like gene (CHD1L) is a new oncogene which has been confirmed to be crucial to the progression of many solid tumors. In the present study, the expression of CHD1L was found to be upregulated in intrahepatic cholangiocarcinoma (ICC), which was significantly associated with histological differentiation (P=0.011), vascular invasion (P=0.002), lymph node metastasis (P=0.008) and TNM stage (P=0.001). Kaplan-Meier survival analysis revealed that ICC patients with positive CHD1L expression had shorter overall and disease-free survival than those with negative CHD1L expression. Functional study found that CHD1L exhibited strong oncogenic roles, including increased cell growth by CCK-8 assay, colony formation by plate colony formation assay, G1/S transition by flow cytometry and tumor formation in nude mice. In addition, RNAi-mediated silencing of CHD1L inhibited ICC invasion and metastasis by wound healing, Transwell migration and Matrigel invasion assays in vitro and in vivo. Collectively, our results show that CHD1L is upregulated and promotes the proliferation and metastasis of ICC cells. CHD1L acts as an oncogene and may be a prognostic factor or therapeutic target for patients with ICC.